PENDAMPINGAN KESIAPTERAPAN DESA SIAGA DAN PEMANFAATAN RUMAH PINTAR SEDERAHANA DI DESA LALANG SEMBAWA KECAMATAN SEMBAWA KABUPATEN BANYUASIN - Marta Pastari; Heni Sumastri; Ratnaningsih Dewi Astuti (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Abstract The condition of Lalang Sembawa Village, which is a division area, still needs guidance from several sectors, especially in the health, education and community economic sectors. Moreover, the condition of the village area has quite a large percentage of poor families and there is a risk of dropping out of school for children from these families. Lalang Sembawa Village is also a fostered partner village of the Palembang Ministry of Health Poltekkes which is planned to become an Alert Village especially in the education and health sectors. Based on the potential and existing problems, several efforts were made to solve the problem: a) Formation and strengthening of standby villages; b) Increasing access to education; through the establishment of a “Simple Smart Home”. Activities related to the strengthening of the standby village are realized through the commitment of the standby village and management can be made. Apart from that, the planned simple smart house has also been realized with the supervisor coming from the local PAUD leaders and teachers. Activities focused on getting students used to group study and increasing creativity have also been realized. Keywords: Standby Villages, Simple Smart Home, dropping out of school for children